If xy = 1, which is equivalent to x(x – 1)(y + 1)?
1 answer:
Answer:
B) x^2 – 1
Step-by-step explanation:
x(x – 1)(y + 1)
FOIL (x-1)(y+1)
firsy: xy
outer 1x
inner -1y
last (1)(-1) =-1
Add them together xy +x-y-1
x( xy +x-y-1)
Replace xy with 1
x( 1+x-y-1)
x(+x-y)
Distribute
x^2-xy
But xy=1
x^2 -1
You might be interested in
Answer: a and c
Step-by-step explanation:
The answer is the last one
15 + (3/2)t ≤ 12
The answer would be a 3x-4y=-10
Answer:
Area of the lawn = 62493π m^2
Step-by-step explanation: